SCIENTIFIC AND METHODOLOGICAL BASICS OF THE FORMATION OF THE ARCHITECTURE OF THE INFORMATION AND ANALYTICAL SYSTEM FOR SUPPORTING AND MAKING DECISIONS ON THE APPLICATION OF THE NATIONAL GUARD OF UKRAINE DURING THE ACCOMPANIMENT OF SPECIAL LOADS - Semenko, Yevheniy (Honor and Law, 2022)
The article shows that today the National Guard of Ukraine does not have an information and analytical system that would ensure the maintenance of effective decision-making in the process of planning and implementation of operational tasks assigned to it (including the escorting of special cargo by the forces of the National Guard of Ukraine), while using all necessary information sources. The scientific and methodological foundations of the formation of the architecture of the information-analytical system for maintaining and making decisions on the use of the National Guard of Ukraine during the escorting of special cargoes are proposed. The option of applying recursive reduction in the process of forming the architecture of the information-analytical system for maintaining and making decisions for use during the escorting of special cargoes is given. The ontological model of the processes of escorting special cargo by the forces of the National Guard of Ukraine is considered. It was established that the structure of this ontological model includes informational and functional components (models). The information component (model) is used to present and describe information flows, data structures, and software modules in the software system. The functional component (model) is used to present interaction processes, relationships and dependencies of software modules, as well as for a detailed description of the components of the information and analytical system. The essence is revealed and the main stages of the method of forming the architecture of the information and analytical system for maintaining and making decisions for the use of the National Guard of Ukraine during the escorting of special cargoes are given. It was determined that the considered method of forming the architecture of the information-analytical system involves the implementation of such main stages as: structuring of input information (in the form of text) using recursive reduction, building an ontology and ontological model of the processes of escorting special cargo by the forces of the National Guard of Ukraine, and forming the architecture of the researched information- analytical system.